2016
DOI: 10.1159/000443787
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Schistosomiasis: Two Different Outcomes

Abstract: Spinal cord schistosomiasis is difficult to diagnose in nonendemic areas. We report the clinical profile of 2 young Saudi males who presented with myelopathy. The first patient arrived at our hospital relatively late, i.e. 3 months following the presentation of initial symptoms, and had received both pulse steroid therapy and a plasma exchange. Praziquantel was administered late and the patient did not recover. The second case presented early, i.e. within around 8 weeks of initial symptoms. This patient receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In light of the results of this study, it can be concluded that normal MCH in patients during the HD process is due to the administration of several drugs that makes mean capsular hemoglobin normal in HD patients (16). Also, in a previous study done on Chittagong HD patients, Chowdhury et al showed that MCH was 28.79±3.77 pg 17 .…”
Section: Hematology Parametersmentioning
confidence: 51%
See 1 more Smart Citation
“…In light of the results of this study, it can be concluded that normal MCH in patients during the HD process is due to the administration of several drugs that makes mean capsular hemoglobin normal in HD patients (16). Also, in a previous study done on Chittagong HD patients, Chowdhury et al showed that MCH was 28.79±3.77 pg 17 .…”
Section: Hematology Parametersmentioning
confidence: 51%
“…This is likely because changes in plasma volume caused by dialysis machines have a significant impact on red cell sedimentation 11 . However, ESR levels in hemodialysis blood were enhanced by 98%, whereas Alsomaili et al found 79.5 % in patients with chronic renal disease 17 .…”
Section: Hematology Parametersmentioning
confidence: 91%
“…and Mohamed et al. reported a similar case in which radiologic findings of intramedullary‐enhancing lesions mimicked spinal cord tumors 6,7 . In Ahmed et al 2 .…”
Section: Discussionmentioning
confidence: 93%
“…2 While post-mortem studies have indicated a three to four times higher prevalence rate of asymptomatic NS cases, 5 the variability of clinical presentation and low index of suspicion can lead to misdiagnosis, even among symptomatic cases. 2,6,7 Herein, we report a case of conus intramedullary NS that mimicked transverse myelitis, and was misdiagnosed as Guillain-Barre syndrome, and subsequently led to delayed treatment and permanent neurological deficit in a 9-year-old boy.…”
Section: Introductionmentioning
confidence: 96%
“…A progressive neurological decline in the setting of medical treatment failure is an indication of spinal cord biopsy [13]. Some entities on the differential diagnosis of a cervical intramedullary lesion, such as neuroschistosomiasis, are reversible and can be medically treated [14,15]. Schistosoma haematobium and S. mansoni are the most common parasitic infections of the spinal cord, and they can cause acute and chronic spinal complications.…”
Section: Discussionmentioning
confidence: 99%